Birth of projection neurons in the higher vocal center of the canary forebrain before, during, and after song learning. - Alvarez-Buylla, A (1988)
The higher vocal center (HVc) of the canary brain projects to two forebrain nuclei: robustus archistriatalis (RA) and area X of lobus parolfactorius. The time of birth of HVc neurons projecting to these two regions was determined by combining [3H]thymidine autoradiography and retrograde fluorogold uptake. Birds were sacrificed at 13 months of age, 4 days after fluorogold injections into area X or RA. A single injection of [3H]thymidine in ovo (embryonic day 9) labeled 76% of area X-projecting cells and 0.8% of cells projecting to RA. The great majority of RA-projecting cells were produced during posthatching development (posthatching day 10-240; P10-P240), with a peak at P60 and a hiatus at P120. HVc reaches full adult size by P240, yet at that age the production of new RA-projecting cells continued at a rate comparable to that recorded during posthatching development. Late production of neurons interconnecting two distant regions of the brain may regulate source to target cell population size. Male canaries start to sing at P40. During subsequent months, they imitate external models and their song becomes more structured and stereotyped. At sexual maturity (P240), song is stable. Three interpretations are offered: (i) neurogenesis of RA-projecting cells is related to learning, and learning continues even after achievement of pattern stability; (ii) neurogenesis of RA-projecting cells is not related to learning; (iii) the production of RA-projecting cells serves different purposes during development and after sexual maturity.